2001
DOI: 10.1074/jbc.m107499200
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Regulation of Diverse Gene Products Revealed by mRNA Expression Profiling of Synchronized Fibroblasts

Abstract: Genes under a 24-h regulation period may represent drug targets relevant to diseases involving circadian dysfunctions. As a testing model of the circadian clock system, we have used synchronized rat fibroblasts that are known to express at least six genes in a circadian fashion. We have determined the expression patterns of 9957 transcripts every 4 h over a total period of 76 h using high density oligonucleotide microarrays. The spectral analysis of our mRNA profiling data indicated that ϳ2% (85 genes) of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
3
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 26 publications
2
77
3
1
Order By: Relevance
“…In general, it appears that about 10 % of the genes are circadianly expressed in the liver, heart, and kidneys (Akhtar et al, 2002;Kita et al, 2002;Panda et al, 2002;Storch et al, 2002;Ueda et al, 2002). Interestingly, in the fibroblasts it has been reported that fewer than 100 genes (or about 2% of the genes present in these cells) are rhythmically expressed (Duffield et al, 2002;Grundschober et al, 2001). The fact that fibroblasts showed much less rhythmic genes expression than the SCN and/or other tissues, but are similar to what has been observed in the pineal (Humpries et al 2002, and this study) suggests that the reduction in the number of rhythmically regulated genes may be due to the reduction in metabolic and physiological activities in fibroblasts and pinealocytes in comparison with cells in other organs and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it appears that about 10 % of the genes are circadianly expressed in the liver, heart, and kidneys (Akhtar et al, 2002;Kita et al, 2002;Panda et al, 2002;Storch et al, 2002;Ueda et al, 2002). Interestingly, in the fibroblasts it has been reported that fewer than 100 genes (or about 2% of the genes present in these cells) are rhythmically expressed (Duffield et al, 2002;Grundschober et al, 2001). The fact that fibroblasts showed much less rhythmic genes expression than the SCN and/or other tissues, but are similar to what has been observed in the pineal (Humpries et al 2002, and this study) suggests that the reduction in the number of rhythmically regulated genes may be due to the reduction in metabolic and physiological activities in fibroblasts and pinealocytes in comparison with cells in other organs and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, the DNA microarray technique has been successfully used to study circadian gene expression in the SCN, liver, heart, kidney, and fibroblasts (Grundschober et al, 2001;Akhtar et al, 2002;Duffield et al, 2002;Kita et al, 2002;Panda et al, 2002;Storch et al, 2002;Ueda et al, 2002). The picture that is emerging from these studies indicates that in each tissue or organ a certain number of genes (approximately 2-10 %) are under circadian control.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of peripheral oscillators to maintain circadian rhythms in the absence of a central pacemaker has been further demonstrated as cultured fibroblasts displayed sustained rhythms in gene expression (3,17) and cultured murine bone marrow progenitors displayed sustained rhythms in response to hematopoietic growth factors (8). Nevertheless, these rhythms tended to fade away unless a stimulation (glucocorticoid, serum shock) or an environmental 24-h cycle (temperature, light) was introduced after a few days in culture, suggesting the need for a regular resetting of free-running peripheral oscillators in order for their coordination to be maintained (2,3,9,21,49).…”
Section: Discussionmentioning
confidence: 99%
“…We selected cell cycle phase distribution in bone marrow and dihydropyrimidine dehydrogenase (DPD) mRNA expression in liver as determinants of 5-fluorouracil tolerability (17,40,45,51) and reduced glutathione (GSH) in liver as a determinant of platinum complex tolerability (4,6,7,28).…”
mentioning
confidence: 99%
“…Components of a molecular clock underlying rhythmic gene expression have been characterized in neurons of the suprachiasmatic nucleus (SCN) [23,24], in liver [23][24][25][26][27], heart [26], synchronized fibroblasts [28], adipose tissue [29], adrenal gland [30], skeletal muscle [31], pituitary [32] and pineal [33] glands, calvarial bone [34], as well as in epithelial cells of lung [35,36] and gastrointestinal tract [37][38][39]. In order to ensure proper temporal organization in metabolism and behavior at the level of an organism, the multiple tissue-specific transcriptional oscillations have to be synchronized with the natural 24-hr cycle.…”
Section: Circadian Clock Organizationmentioning
confidence: 99%